Marine acoustics : direct and inverse problems - Buchanan, James L. (Society for Industrial and Applied Mathematics, 2004)
This book presents current research trends in the field of underwater acoustic wave direct and inverse problems. Until very recently, little has been published concerning model-based inversions of the boundaries and material constants of finite-sized targets located either in the water column or the sediments. This text is the first to investigate inverse problems in an ocean environment with a heavy emphasis placed on the description and resolution of the forward scattering problem.
Keywords: Underwater acoustics.; elektronické knihy; electronic books